The problems of enduring cultural properties in Jaffna - Ahilan, P. (UNESCO, 2006)
The psycho-physical phenomena produced mainly by the geo-historical context of particular societies provided the basis for the formation of their cultures. The living nature of culture produces numerous subjects and objects of society at a given time and space. They stand for the history, memory and identity of a particular society. The background of social change conditions the problem of the continued existence of the cultural goods and sites. Therefore countries developed the notion and mechanisms of preservation of cultural products as an inevitable part of their countries empowerment. The written history of Jaffna commences from the 16th Century. Much of the earlier documented history and most of the heritage properties may have been displaced due to the existing material conditions and uncertain political conditions. Jaffna was under the rule of the Portuguese, the Dutch and the English for 500 years. Through the interaction with these colonial cultures, Jaffna produced unique characters and styles in its material and non-material cultures. Most unfortunately Nationalist historians neglected the artistic and historical achievements of Colonial Jaffna. In the last quarter of years in Jaffna, which is mainly govern by the ethnic conflict, civil war and the changes in class structure, its interests and priorities of life, have rapidly increased the problems of protecting and preserving heritage properties. The heritage sites and properties became a target of war. Expansion of high security zones, displacement of people, and the absence of museums and other Heritage management institutions further aggravated the situation. The opening of A9 the road has introduced a new dimension. It opened up an avenue to the Colombo based antique markets and new fashions of material culture of plastic. This brought in people who influenced the demolition, selling, looting of cultural prosperities rapidly. As a response to this unprecedented situation of destruction, Kalai Vatam (Art Circle), students of Art history and the staff members of Department of Fine Arts, University of Jaffna started a campaign programme to make the public aware of the importance of preserving heritage properties. As part of their campaign they mobilize 69 the people through newspaper, pamphlet, picture postcards and life performance in the main corners of the Jaffna peninsula and did a door to door survey in some sensitive areas to educate the people. The main focus of the programme is on the notion of heritage properties and its importance in the cultural history and cultural identity. My paper states the background of enduring the heritage property in Jaffna during and the war and post war situations and one strategy used to preserve these properties. This paper also tries to explore the role of Government and the Non Government organization in the process of preservation, conservation and documentation of artifacts touched and untouched by the war.